Numerical Study of Single Cavity at Inlet Mach of 2 for Non Reactive Jets In Scramjet Combustor - Ajin Branesh (International Journal of Advanced Science and Technology, 2020)
The research for implementing favourable techniques and methods for hypersonic transportation involves scramjet propulsion where the combustion is finished within a few milliseconds which can add a huge amount of rich mixture inside the combustor section. The Scramjet combustor flow dynamics is investigated for turbulence generation and air holding capability using axis symmetric cavity sections employed inside the combustor model. Here the incoming mach is set to be 2 for which the recirculation and flow instability caused are predicted for a total of 21 cases and performed to recommend an optimum solution of implementing single cavity on either side from the combustor axis. Recirculation zones thus formed will pave way for enhanced mixing and atomization behaviour prominently. In this work, the cavity with L/D 3 and 5 are considered with ramp angles 30, 45 and 60 degrees which are studied for ensuring increment in turbulence and maintaining mach inside the combustor. Rectangular cavities with the above configurations are employed for two dimensional studies that are compared to a model without having cavity section on it. The shock train region formed because of the cavity implementation allows the upcoming flow stream to hold for an extra second that may ensure holding techniques.